Splitting spacetime and cloning qubits: linking no‐go theorems across the ER=EPR duality. Issue 11 (2nd November 2015) - Bao, Ning; Pollack, Jason; Remmen, Grant N.
Abstract : The paper analyzes the no‐cloning theorem in quantum mechanics through the lens of the proposed ER = EPR (Einstein‐Rosen = Einstein‐Podolsky‐Rosen) duality between entanglement and wormholes. In particular, the authors find that the no‐cloning theorem is dual on the gravity side to the no‐go theorem for topology change, violating the axioms of which allows for wormhole stabilization and causality violation. Such a duality between important no‐go theorems elucidates the proposed connection between spacetime geometry and quantum entanglement. Abstract : We analyze the no‐cloning theorem in quantum mechanics through the lens of the proposed ER=EPR (Einstein‐Rosen = Einstein‐Podolsky‐Rosen) duality between entanglement and wormholes. In particular, we find that the no‐cloning theorem is dual on the gravity side to the no‐go theorem for topology change, violating the axioms of which allows for wormhole stabilization and causality violation. Such a duality between important no‐go theorems elucidates the proposed connection between spacetime geometry and quantum entanglement.